PHYSICAL WATER QUALITY RESPONSE TO RAINFALL OF BETON KARST SPRING AT GUNUNGKIDUL REGENCY -YOGYAKARTA INDONESIA - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Beton karst spring is located in the Ponjong sub District GZiTlungkidul Regency, at the western part oj Bribin undergorwzd river catchment area. The purpose oj this study are: I) to know the variations oj rainfall and discharge in the research area, 2) to know the characteristics of the physical water quality of Beton spring and 3) to determine the relationship between the variations of the rainfall toward the discharge and the physical water quality of Beton spring. This study uses survey methods and the techniques oj data collection using sample by purposive sampling. The variables are rainfall (the depth and intensity), spring discharge and physical water quality oj spring (EC, 1: TDS, turbidity). The data analysis is conducted graphically and descriptively to explain the relationship between the variations oj rainfall to the discharge and physical water quality oj spring. The results show the rainfall has variations include the pattern, events and the amount of rainjall. Beton spring has high discharge variations. The physical water quality oj the spring meets to the water quality standards according to the Government Regulation number 82 years 2001. The strong correlation between rainJall variations to the discharge and the physical water quality oj Beton spring can be seen clearly. It is reflected from the high value oj R2. Key words: springs, rainfall, discharge, water quality, response